AKAR MODERASI BERAGAMA DALAM KITAB AL-RISALAH IMAM SYAFI’I - munim, abdul; Tanzilulloh, M. Ilham (Al-Syakhsiyyah: Journal of Law and Family Studies, 2021)
This research aims to analyze how the scholarly challenges in composing Ar-Risalah, to understand Ar-Risalah's criticism of extremism in diversity at that time, and to identify offers from Ar-Risalah that can be identified as moderation. This study uses qualitative research methods, with a philosophical approach. The primary data source is the book Ar-RisÄlah by Muhammad bin Idris ash-Shafi'i, also known as Imam Shafi'i, edited by Ahmad Muhammad Syakir. The findings of this research indicate that at the time of the legal discourse tension between the opposing factions, usul (fundamentals) had not yet emerged as a discipline because its epistemological framework was unclear. Al-Risalah begins with an exposition on the epistemological aspects of Islamic law. The legal methodological concept offered by ash-Shafi'i aims to control excessive rationality that demands change and excessive textualism that demands certainty toward a moderate position, as written in the book Ar-Risalah.